Safe Operation Area of Energy-Storage-Free Dynamic Voltage Restorer - Mingxing ZHU; Xuan LU; Huaying ZHANG; Qing WANG (Zhongguo dianli)
Energy-storage-free dynamic voltage restorer (DVR) is a common device used to solve voltage sag problems in engineering, but its actual operation is limited by the parameters of application scenarios. To solve this problem, an algorithm is proposed for the safe operation area of energy-storage-free DVR, which can calculate the maximum compensation capacity of energy-storage-free DVR based on the application scenario parameters, thus standardizing the application of energy-storage-free DVR in engineering. Firstly an impedance model of the system is built based on the relationship between the cable, transformer and the safety compensation range of the energy-storage-free DVR device. Secondly, the secondary voltage sag caused by the compensation process of the energy-storage-free DVR is analyzed, and the safe operation area of the energy-storage-free DVR device is calculated based on the overload capacity of the system. Finally, the calculation method of the safe operation area is further clarified by simulation analysis. The proposed calculation method determines the safe operation area of the new energy-storage-free DVR under the constraint conditions of the application scenarios, which provides a theoretical reference for the effective application of the energy-storage-free DVR.